Economic development and crime in Brazil: a multivariate and spatial analysis - Barros, Pedro Henrique Batista de; Baggio, Isadora Salvalaggio; Stege, Alysson Luiz; Hilgemberg, Cleise Maria de Almeida Tupich (Revista Brasileira de Estudos Regionais e Urbanos, 2019)
This paper aimed to analyze the spatial distribution of crime in the 5,565 Brazilian municipalities and to investigate its relationship with local economic development. More specifically, we analyze the presence of spatial dependence and heterogeneity as well as spatial clusters among the municipalities, using Exploratory Spatial Data Analysis (ESDA) and homicide rate as a proxy for crime. Due to the large number of socioeconomic variables identified in the literature as important to explain crime, we created an Economic Development Index (EDI) for Brazilian municipalities that synthesizes all possible influences, using factor analysis from multivariate statistics. We also grouped municipalities with dissimilar crime and economic development characteristics via cluster analysis. The results show that both economic development and crime are spatially concentrated in Brazil, suffering from spatial dependence. In addition, the EDI and crime are negatively associated for most Brazilian municipalities both in spatial and cluster analysis, indicating that economic development is a crime inhibitor. However, there are some municipalities where economic development is not capable of barring crime advancement, which requires special attention by researchers and public agents.